PENGARUH BIAYA IJARAH TERHADAP KEPUTUSAN NASABAH MELAKUKAN GADAI EMAS DIPEGADAIAN SYARIAH - Mulyani Rizki (Jurnal Ekonomi Bisnis dan Akuntansi, 2021)
Ijarah fee is a rental fee that must be paid by customers in conducting gold pawn transactions. The amount of the ijarah fee is determined based on the results of the estimated value of gold, so that the relatively low cost of ijarah for customers will make it easier for customers to do financing. The cost of ijarah (rent) according to Muhammad Ngasifudin is the cost of renting a place provided by the pawnshop for goods that have been pawned by the customer.27 So, the cost of ijarah at a sharia pawnshop is the rental fee for the goods that are pawned as a place to store the goods as long as the goods have not been redeemed. by the owner. Judging from the above phenomenon, the Ijarah Fee can be taken into consideration for customer decision making to pawn gold at a sharia pawnshop. The purpose of this study was to determine how the influence of Ijarah Fees on the customer's decision to pawn gold at the Sharia Pawnshop. The number of samples in this study was 88 respondents, this study used a quantitative approach. The data collection technique in this study used a questionnaire, and the sampling technique used the incidental sampling method using the slovin formula. The data obtained were then processed using the SPSS 25 application. The results of this study indicate that the value of tcount (3.085) > ttable (1.988) and a significance value of 0.003 <0.05, which means that partially the ijarah fee variable has a positive and significant effect on the customer's decision variable in pawning gold at Pegadaian Syariah.